Life cycle benefits of enzymatic biodiesel co-produced in palm oil mills from sludge palm oil as renewable fuel for rural electrification. (1st November 2022) - Gourich, Wail; Chan, Eng-Seng; Ng, Wei Zhe; Obon, Aaron Anthony; Maran, Kireshwen; Ong, Yi Hui; Lee, Chin Loong; Tan, Jully; Song, Cher Pin
Graphical abstract: Highlights: A case study on biodiesel production in a palm oil mill in Kalimantan was conducted. Sludge palm oil is converted to biodiesel via enzymatic route using liquid lipase. Enzymatic biodiesel produced in the palm oil mill is used for rural electrification. The LCA compared electrification with commercial B30 diesel and enzymatic biodiesel. Electrification using enzymatic biodiesel shows improved life cycle benefits. Abstract: The lack of reliable electricity access persists as a global issue, particularly in rural areas. Off-grid electrification using diesel generators is commonly practiced by rural communities, but using diesel is not environmentally sustainable. In this paper, we proposed a new concept to create renewable energy access in rural areas by co-producing biodiesel in rural palm oil mills using non-edible sludge palm oil (SPO) as a feedstock. We performed a case study based on a medium-sized palm oil mill in Central Kalimantan, the Indonesian part of Borneo. A one-pot batch process catalyzed by low-cost liquid lipase was selected to convert SPO into biodiesel. To determine the environmental viability of this rural electrification concept, we compared two electrification routes using different generator fuels (i.e., commercial B30 diesel and enzymatic biodiesel co-produced in palm oil mills from SPO) via a cradle-to-grave comparative life cycle assessment. Our results revealed that electrification using enzymatic biodiesel offers significantly improved climate benefits compared to commercial B30 diesel. Furthermore, assuming that a mill processing 40 tonnes of fresh fruit bunches daily were to adopt this concept, its biodiesel co-production facility would be able to support about 940 surrounding households. Conclusively, this electrification concept is feasible and can be readily implemented in many developing and under-developed palm oil producing countries.